Page 1

x(x + 4) = 396 x² + 4x = 396 x² + 4x – 396 = 0 (x + 22) (x – 18) = 0 x + 22 = 0 x – 18 = 0 x = -22 x = 18

x² - 7x = 0 x(x – 7) = 0 x=0 x–7=0 x=0 x=7

x² + 5x = 0 x(x + 5) = 0 x=0 x+5=0 x=0 x = -5

3x² - 48 = 0 x² - 16 = 0 x² + 0x - 16 = 0 (x + 4) (x – 4) = 0 x+4=0 x–4=0 x=-4 x=4


5x² - 75 = 0 x² - 15 = 0 x² + 0x - 15 = 0 (x + 3.87) (x – 3.87) = 0 x + 3.87 = 0 x – 3.87 = 0 x = -3.87 x = 3.87

x² + 3x – 1 = 0 a=1 b=3 c = -1

x = -b + – b² - 4ac 2a x = -3 + – 3² - 4(1)(-1) 2(1)

x(x + 5) = 150 x² + 5x = 150 x² + 5x – 150 = 0 (x + 15) (x – 10) = 0 x + 15 = 0 x – 10 = 0 x = -15 x = 10

y² + 3y – 1 = 0 a=1 b=3 c = -1

x = -3+ – 9+4 2 x = -3 + – 13 2 x = -3 + – 3.6 2

y = -b+ – b² - 4ac 2a y = -3+ – 3² - 4(1)(-1) 2(1) y = -3+ – 9+4 2 y = -3+ – 13 2 y = -3 + – 3.6 2

x = -3 + 3.6 2

x = -3 - 3.6 2

y = -3 + 3.6 2

y = -3 - 3.6 2

x = 0.6 2 x = 0.3

x = -6.6 2 x = -3.3

y = 0.6 2 y = 0.3

y = -6.6 2 y = -3.3


4x² - 25 = 0 (2x + 5) (2x – 5 ) = 0 2x + 5 = 0 2x – 5 = 0 2x = -5 2x = 5 x = -5 x=5 2 2 x = -2.5 x = 2.5

9y² - 16 = 0 (3y + 4) (3y – 4 ) = 0 3y + 4 = 0 3y – 4 = 0 3y = -4 3y = 4 y = -4 y=4 3 3 y = -1.33 y = 1.33

3(x – 6)² = 108 3(x – 6)(x – 6) = 108 (x – 6)(x – 6) = 108 3 (x – 6)(x – 6) = 36 x² - 6x - 6x + 36 = 36 x² - 12x + 36 = 36 x² - 12x + 36 – 36 = 0 x² - 12x = 0 x(x – 12)=0 x=0 x – 12 = 0 x=0 x = 12

3(x + 2)(x + 3) = 60 (x + 2)(x + 3) = 60 3 (x + 2)(x + 3) = 20 x² + 3x + 2x + 6 = 20 x² + 5x + 6 = 20 x² + 5x + 6 – 20 = 0 x² + 5x - 14 = 0 (x + 7) (x – 2) = 0 x+7=0 x–2=0 x = -7 x=2

ecuaciones del ejercicio V (en la libreta)  

ecuaciones del ejercicio V (en la libreta)